Characteristics of Bladder Cancer in Dr. Sardjito General Hospital Yogyakarta: a 5-Year Report - Fitra Hardian Prisnamurti; Ahmad Zulfan Hendri; Aria Danurdoro (Indonesian Journal of Cancer, 2022)
Background: Bladder cancer is the eleventh most common malignancy worldwide and the sixth cancer in men. Bladder cancer shows a male predominance with a sex ratio of 4:1. Most bladder cancers are transitional cell carcinoma, and the other tumors are squamous cell carcinoma, adenocarcinoma, and rare entities like small cell carcinoma. Clinical stage and grade are the most critical determinants of the prognosis of bladder cancer. Therefore, this study aims to evaluate the characteristics of bladder cancer in Dr. Sardjito General Hospital, Indonesia. Methods: We reviewed the medical records of patients with bladder cancer admitted to Dr. Sardjito General Hospital Yogyakarta from January 2015 until December 2020. The data were about demographic characteristics, clinical presentation and staging, grading and staging based on pathological examinations results, and cancer management. Results: This study found 282 patients with bladder tumors. Fifty patients did not meet the inclusion criteria so the remaining 232 patients consisted of 169 male patients (72.8%) and 62 female patients (27.2%). The stages of tumors when the patients first came in were T1 diagnosed in 46 patients (22.7%), T2 diagnosed in 81 patients (40%), T3 diagnosed in 11 patients (5.4%), and T4 diagnosed in 64 patients (31.6%). A total of 30 patients were found to have secondary bladder tumors. The pathological anatomy results showed that 177 patients (76.2%) had transitional cell carcinoma and 33 patients adenocarcinoma (14.2%). All patients had undergone Transurethral Resection of Bladder Tumor (TURBT) for diagnosis and staging, followed by definitive treatment. It consisted of TURBT and chemotherapy bladder instillation in 46 patients (19.8%), radical cystectomy in 84 patients (36.2%), partial cystectomy in 4 patients (1.7%), and multimodal therapy (en-bloc transurethral resection of bladder tumors (ERBT) and chemotherapy) in 26 patients (11.2%). There were 72 patients (31%) who underwent TURBT alone. Conclusions: From a 5-year study, we found similar results with previous studies that the most common bladder histopathological result is urothelial carcinoma. However, most patients presenting to our hospital have higher stages and grades, requiring radical treatment. These differences warrant a larger and more comprehensive, multi-center study in Indonesia.